Detection of small lattice strains using beam rocking on a nuclear microprobe - de Kerckhove, D; Breese, M; Wilkinson, A; Grime, G (1998)
Beam rocking is a new technique in nuclear microscopy which has been developed at the Oxford nuclear microprobe to produce angle-resolved channelling information from small areas of crystalline material without any rotation or translation of the sample. This paper describes a different application of beam rocking whereby a focused 3 MeV proton beam has been used to detect and quantify small interface rotation angles in strained Si1-xGex/Si samples with 0.015 < x < 0.175, where the sample has been selectively etched to expose the underlying substrate. By eliminating possible rotation errors due to translation of the sample stage or backlash in the gears of a goniometer, small rotation angles have been measured, and these are found to be in good agreement with electron back scatter diffraction (EBSD) results. It is also shown that, by minor modifications to the scanning or focusing system, the area over which the rocked beam moves on the sample surface can be reduced to <6 mu m for a similar to 3 degrees angle. In a further development of the Oxford nuclear microprobe scanning system, it is shown how the addition of a second set of scanning coils eliminates previous problems of dechannelling due to angular tilting in spatially resolved channelling scanning transmission ion microscopy (CSTIM) images. (C) 1998 Elsevier Science B.V.